Thermal performance of thermoplastic polyurethane composites with microencapsulated piperazine pyrophosphate - Hu, Shuang; Peng, Jianwen; Tian, Jianjun; Xiao, Chong (Frontiers in Materials, 2023)
A novel flame retardant, Melamine formaldehyde microencapsulated piperazine pyrophosphate (MFPAPP), was synthesized and investigated for its efficacy in improving the thermal and flame retardant properties of thermoplastic polyurethane (TPU). When TPU was incorporated with 30wt% MFPAPP, the limiting oxygen index (LOI) value of the TPU/MFPAPP composite was increased to 38.8%, achieving V-0 rating. Thermogravimetric analysis (TGA) results confirmed that MFPAPP significantly enhanced the thermal stability of TPU/MFPAPP composite, as indicated by the increased char residue at 800℃, which was up to 22.4wt%. Compared with the pure TPU samples, the peak heat release rate (PHRR) and total heat release (THR) of TPU/MFPAPP30 were reduced by 53% and 45%, respectively. TPU/MFPAPP10 maintained a V-0 rating after a water immersion test, whereas TPU/PAPP degraded to V-2 rating. Scanning electron microscopy (SEM), Raman spectra, and X Ray photoelectron spectroscopy analyses revealed that MFPAPP promoted the formation of heat-resistant and dense expanded carbon layers. In summary, MFPAPP demonstrated remarkable flame retardancy and thermal stability, making it an ideal candidate for enhancing the fire safety of thermoplastic polyurethane materials.